Gastric Ulcer Bleeding associated with a Left Gastric Artery Pseudoaneurysm - Seokin Kang; Yuri Kim; Kee Don Choi (Yong Chan Lee, 2021)
A left gastric artery (LGA) pseudoaneurysm is known to occur as a complication of abdominal surgery, trauma, or pancreatitis. However, an LGA pseudoaneurysm presenting with gastrointestinal bleeding is rare. A 77-year-old man complained of dizziness and three episodes of melena in the last 24 hours. He did not have a history of surgery, trauma, or pancreatitis. He underwent primary coronary intervention for unstable angina and started dual antiplatelet therapy 1 month prior. Esophagogastroduodenoscopy (EGD) revealed a 3-cm ulcer in the lesser curvature of the gastric high body with a pulsating subepithelial tumor-like lesion in the ulcer. Hemostasis was achieved endoscopically. Three days after the endoscopic hemostasis, hematemesis and hypovolemic shock occurred. Emergent angiography of the superior mesenteric artery revealed an LGA pseudoaneurysm with extravasation. Coil embolization was successfully performed. Three days after the angiographic embolization, EGD revealed improvement of the gastric ulcer, which was covered with exudate, and disappearance of the subepithelial tumor-like lesion. At the 2-month follow-up, EGD showed that the ulcer was in the healing stage.